Factors Associated with Non-Participation and Non-Adherence in Directly Observed Mass Drug Administration for Malaria in The Gambia. - Susan Dierickx; Charlotte Gryseels; Julia Mwesigwa; Sarah O'Neill; Melanie Bannister-Tyrell; Maya Ronse; Fatou Jaiteh; René Gerrets; Umberto D'Alessandro; Koen Peeters Grietens (PLoS ONE)
Introduction The potential benefits of Mass Drug Administration (MDA) for malaria elimination are being considered in several malaria endemic countries where a decline in malaria transmission has been reported. For this strategy to work, it is important that a large proportion of the target population participates, requiring an in-depth understanding of factors that may affect participation and adherence to MDA programs. Methodology This social science study was ancillary to a one-round directly observed MDA campaign with dihydroartemisinin-piperaquine, carried out in 12 villages in rural Gambia between June and August 2014. The social science study employed a mixed-methods approach combining qualitative methods (participant observation and in-depth interviewing) and quantitative methods (structured follow-up interviews among non-participating and non-adhering community members). Results Of 3942 people registered in the study villages, 67.9% adhered to the three consecutive daily doses. For the remaining villagers, 12.6% did not attend the screening, 3.5% was not eligible and 16% did not adhere to the treatment schedule. The main barriers for non-participation and adherence were long and short-term mobility of individuals and specific subgroups, perceived adverse drug reactions and rumors, inconveniences related to the logistics of MDA (e.g. waiting times) and the perceived lack of information about MDA. Conclusion While, there was no fundamental resistance from the target communities, adherence was 67.9%. This shows the necessity of understanding local perceptions and barriers to increase its effectiveness. Moreover, certain of the constraining factors were socio-spatially clustered which might prove problematic since focal areas of residual malaria transmission may remain allowing malaria to spread to adjacent areas where transmission had been temporarily interrupted.